ANALISIS KIMIA DAN MIKROBIOLOGIS BELACAN DEPIK (Rasbora tawarensis), PASTA IKAN FERMENTASI TRADISIONAL GAYO - MURNA MUZAIFA MUZAIFA ' (Jurnal Sagu, 2015)
ABSTRACTBelacan depik is a traditional food of Gayonese obtained by fermentation of depik (Rasbora tawarensis) fish.The aim of this research were to analyze the chemical and microbiological characteristics of belacan depik.This study was explorative study using sample belacan depik from traditional market in Takengon, CentralAceh. The parameters analyzed were chemical (content of water, protein, fat, ash, carbohydrate) andmicrobiological (total lactic acid bacteria) analysis. The results show that belacan depik had 57,93% ofwater, 14,46 % of protein, 5,18% of fat and 14,21% of carbohydrate. Belacan production is spontaneousfermentation, without addition of microbial culture. Total lactic acid bacteria was 6,3 x108 CFU/gram. Thisis an indication that belacan depik is lactic acid bacteria fermented product.Key words: belacan depik, gayo, fermentation, lactic acid bacteria